2020
DOI: 10.4178/epih.e2020006
|View full text |Cite
|
Sign up to set email alerts
|

An interim review of the epidemiological characteristics of 2019 novel coronavirus

Abstract: OBJECTIVES: The 2019 novel coronavirus (2019-nCoV) from Wuhan, China is currently recognized as a public health emergency of global concern.METHODS: We reviewed the currently available literature to provide up-to-date guidance on control measures to be implemented by public health authorities.RESULTS: Some of the epidemiological characteristics of 2019-nCoV have been identified. However, there remain considerable uncertainties, which should be considered when providing guidance to public health authorities on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 18 publications
3
140
1
12
Order By: Relevance
“…The reporting rate after 17 January 2020 has been considered to have increased 21-fold in comparison to the situation in the first half of January 2020 [8]. The average incubation period is estimated to be 5.2 days, with significant variation among patients [9], and it may be capable of asymptomatic spread [10,11]. Symptoms of infection include fever, chills, cough, coryza, sore throat, breathing difficulty, myalgia, nausea, vomiting, and diarrhea [12].…”
Section: Introductionmentioning
confidence: 99%
“…The reporting rate after 17 January 2020 has been considered to have increased 21-fold in comparison to the situation in the first half of January 2020 [8]. The average incubation period is estimated to be 5.2 days, with significant variation among patients [9], and it may be capable of asymptomatic spread [10,11]. Symptoms of infection include fever, chills, cough, coryza, sore throat, breathing difficulty, myalgia, nausea, vomiting, and diarrhea [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms included cough (46.3%), upper airway congestion (61.5%), myalgia (23.1%) and headache (23.1%) [9] . Although some of the epidemiological characteristics were identified, considerable uncertainties are still present and additional studies are needed with detailed information from confirmed cases [32] .…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…4,7,9,10 cases were aged between 25 and 62 years. 16 Regarding elderly patients infected with SARS-CoV-2, one study showed that 14.6% (6 in 41) of patients were aged ≥ 65 years, 13 while another study showed that 15.2% (15 in 99) patients were aged ≥ 70 years, among pneumonia cases. 12 In addition, two non-peer-reviewed studies showed only 153 (15.1%) patients were elderly patients aged ≥ 65 years, 11 and 407 (10.1%) patients were aged > 70 years.…”
Section: Severity Of Covid-19mentioning
confidence: 99%
“…8 Regarding patient sex ratio, male sex comprised more than half of the cases in most COVID-19 studies [11][12][13][14] and the proportion of males ranged from 51.4% to 73.2%. 8,[11][12][13][14]16 Initially, approximately half of the cases had Huanan seafood market exposure and animal-to-human transmission was suspected. 12,13 However, fewer cases had exposure to this seafood market and an increasing number of cases demonstrated human-to-human transmission.…”
Section: Severity Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation